Effect of resistance training on blood glucose fluctuation and painful diabetic peripheral neuropathy in adults with type 2 diabetes mellitus - Suparta Suparta; Sulaeman Sulaeman; Roni Roni; Asnuddin Asnuddin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Diabetes Mellitus (DM) Type 2 is a chronic metabolic disease that can cause serious complications, such as peripheral circulatory disorders and diabetic foot ulcers, if blood glucose levels are not controlled. Resistance Exercise is one form of physical activity intervention that has the potential to prevent these complications. Purpose: To determine the effect of resistance training on blood glucose fluctuation and painful diabetic peripheral neuropathy in adults with type 2 diabetes mellitus. Method: This study used a pre-experimental design with a two-group pretest-posttest design. A total of 60 participants were selected through simple random sampling, divided into two groups: intervention (n=30) and control (n=30). The intervention group was given Resistance Exercise for a certain period, while the control group was not given any treatment. Data were analyzed using the Paired t-Test . Results: There were significant differences in the intervention group before and after intervention on blood glucose levels (p=0.000), peripheral blood circulation (p=0.000), and leg pain (p=0.000). Meanwhile, the control group did not show significant differences in peripheral blood circulation (p=0.161) and leg pain (p=0.083). Conclusion:​​ Resistance Exercise is effective in lowering blood glucose levels, improving peripheral blood circulation, and reducing leg pain in patients with Type 2 DM. This intervention is recommended as part of DM management at the primary care level.